Selection of Model For Predicting Runoff A Case Study at Saleran watershed (Punjab) - Narda, N.K.; Sur, H.S.; Khandelwal, M.K.; Sabu, M.S. (Journal of Soil and Water Conservation, 2022)
The higher coefficient of determination obtained in case of the Artificial Neural Network, the SWMHMS and the USDA, SCS, Curve Number Technique offers three alternatives to predict runoff in the region. One of the methods may be adopted to predict runoff in watershed with similar characteristics.